2016
DOI: 10.1146/annurev-nutr-071715-051030
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum–Associated Degradation and Lipid Homeostasis

Abstract: The endoplasmic reticulum is the port of entry for proteins into the secretory pathway and the site of synthesis for several important lipids, including cholesterol, triacylglycerol, and phospholipids. Protein production within the endoplasmic reticulum is tightly regulated by a cohort of resident machinery that coordinates the folding, modification, and deployment of secreted and integral membrane proteins. Proteins failing to attain their native conformation are degraded through the endoplasmic reticulum–ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 214 publications
1
133
0
Order By: Relevance
“…Consistent with this possibility, a recent study in yeast demonstrated that hairpin motifs were sufficient to target proteins for degradation through ERAD [106]. ERAD enables the cytosolic degradation of proteins from the early secretory pathway by mediating their recognition, ubiquitination, and subsequent extraction from the ER membrane by the AAA ATPase VCP (Cdc48 in yeast) [109111]. Deletion of the yeast, polytopic ERAD E3 ligase Doa10p or its cognate E2 ubiquitin-conjugating enzymes Ubc6p or Ubc7p stabilized the Class I LD protein Pgc1p in the ER [106].…”
Section: Connections Between Lds and The Ubiquitin-proteasome Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…Consistent with this possibility, a recent study in yeast demonstrated that hairpin motifs were sufficient to target proteins for degradation through ERAD [106]. ERAD enables the cytosolic degradation of proteins from the early secretory pathway by mediating their recognition, ubiquitination, and subsequent extraction from the ER membrane by the AAA ATPase VCP (Cdc48 in yeast) [109111]. Deletion of the yeast, polytopic ERAD E3 ligase Doa10p or its cognate E2 ubiquitin-conjugating enzymes Ubc6p or Ubc7p stabilized the Class I LD protein Pgc1p in the ER [106].…”
Section: Connections Between Lds and The Ubiquitin-proteasome Systemmentioning
confidence: 98%
“…Organelles contain specialized pathways (e.g. ER-associated degradation [ERAD] [109111]) that mediate the recognition of their respective proteomes for degradation. These include quality control pathways that degrade misfolded and damaged proteins (e.g.…”
Section: Connections Between Lds and The Ubiquitin-proteasome Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nearly 70 human diseases have been linked to ERAD (2). While the biochemical processes of ERAD have been well characterized in the last two decades (8-10), the physiological significance of mammalian ERAD at the organismal level remains vague. This is an especially challenging problem given a vast number of different cell types and their crosstalk in mammals.…”
mentioning
confidence: 99%
“…To ensure the fidelity of the secretory proteome, the ER has evolved a quality control system that detects terminally misfolded and unoligomerized proteins and targets them for clearance via a process known as ER-associated degradation (ERAD; Olzmann et al. , 2013a; Christianson and Ye, 2014; Stevenson et al. , 2016).…”
Section: Introductionmentioning
confidence: 99%